HUBUNGAN BEBAN KERJA PERAWAT DENGAN PELAKSANAAN PENDIDIKAN KESEHATAN DALAM PENCEGAHAN RISIKO JATUH DI RUANG RAWAT INAP RUMAH SAKIT - Eva Yuliatin; Susilaningsih Susilaningsih; Yeni Fitria (Jurnal Ilmiah Kesehatan Media Husada, 2020)
Introduction : Nurse educators have a responsibility to improve patient knowledge, especially in preventing the risk of falls, however this is often constrained by the severity of the nurse's workload. This study aims to know the correlation between nurses' workload and the implementation of health education in preventing the risk of fall in the Inpatient Room of Batu Baptist Hospital. Method:This study uses a correlational method with a cross sectional approach. The sampling used is purposive sampling containing 32 nurse respondents. The data were collected by using questionnaires and observation sheets. Based on the results of research from 18 respondents with heavy workload categories, 14 respondents (43.7%) did poor health education and 4 respondents (12.5%) carried out good health education . Results and Analysis: The data were processed by using the Spearman Rank test with the results of probability (sig.) 0,000 and the value of r count of 0.845 including the strength of coefficient. It can be concluded that there is a significant correlation between the workload of nurses and the implementation of health education. Discussion:The heavier the workload of nurses, the worse implementation of health education is . Hospital Management needs to analyze nurses' workload objectively so that the constraints in the implementation of health education can be minimized.